Pemertahanan Bahasa Jawa dalam Ranah Keluarga oleh Transmigran Jawa di Kampung Wadio, Distrik Nabire Barat, Nabire, Papua Tengah - Winda Woro Mahmudah; Kisyani Laksono; Mulyono (LP. Ma'arif Janggan Magetan, 2023)
Javanese language has the largest number of speakers in Indonesia. The Javanese are scattered in almost every region in Indonesia, including in Papua which has settlements for transmigrants. Nabire is one of the areas in Central Papua that is designated for the transmigration program, so that many villages have a large population of Javanese speakers. However, as Nabire developed, there were more and more immigrants, not only from the Javanese. So that to communicate, people choose to use Indonesian or Papuan Malay so that they can be accepted and understood by all ethnic groups. Now, the use of Javanese in transmigrant villages is mixed with Indonesian, Papuan Malay, and other regional languages. However, Javanese is still often used, especially in the family realm. This study aims to describe the use of Javanese in the family sphere by Javanese transmigrants in Wadio Village, West Nabire District, Nabire, Papua. The research method uses a qualitative descriptive technique with a sample of 105 respondents. Determination of the number of respondents was taken from 10% of the total Javanese population of 1,050 people. The results of this study indicate that there is still language maintenance in the village. In the old group, they have high loyalty with a percentage of 86.75%, while in the young group, it is moderate with a percentage of 51.25%.